Gastrointestinal stromal tumor revealed by hemorrhagic shock - Lemfadli, Yassine; Aouroud, Hala; Jallouli, Abderrahmane; Errami, Adil Ait; Oubaha, Sofia; Samlani, Zouhour; Krati, Khadija (Global Journal of Medical and Clinical Case Reports, 2022)
Gastrointestinal Stromal Tumors (GISTs) are rare tumors of the digestive tract. The small intestine is the second most frequent localization of GIST after the stomach. We report a case of the ileal stromal tumor. The patient was admitted with a picture of hemorrhagic shock due to massive rectal bleeding. The fiberscope performed after stabilization was not objectified at the origin of the document while the CT scan objectified a mass of tissue density at the level of the right iliac fossa. Given the increasing evolution with the recurrence of patients to a target of a laparotomy for diagnostic and therapeutic purposes objectifying the tumor of the right iliac fossa at the expense of the ileum. The surgical procedure consisted of a major segmental resection of the tumor with ileo-ileal anastomosis. The anatomopathological study confirmed the diagnosis of the stromal tumor with good evolution. Through a general review of the literature, we have described the various clinical, para-clinical, anatomopathological, prognostic, and current therapeutic aspects specific to these tumors.